Perception of teachers and students after a program of active breaks at the beginning of the school day: A pilot study in Chile (Research, Society and Development, 2022)
Objective: Determine the perception of teachers and students, after a program of active breaks at the beginning of the class. Methodology: A longitudinal experimental study was carried out. The sample selected was non-probabilistic for convenience. We worked with 56 students of both sexes (34 men and 22 women), from a municipal educational establishment in the city of Talca, aged between 9 and 10 years.  Results: after having carried out the research project, an inclination towards the favorable percentages of agreement (22.6%) and strongly agree (51.9%) was observed. The instrument showed a good reliability capacity (Cronbach's alpha 0.858). Conclusion: The questionnaire used to measure the perception of teachers and students after the active breaks program was valid and reliable, it was also determined that there was a lot of support and input from the participants transmitting satisfaction with the active breaks program. Regarding the perception of the teachers, a broad approval was found for the program product the benefits that they perceived in their students, both in terms of concentration and improvement in their academic performance.